Solar variability effects on climate - Roederer, Juan G. (1994)
One of the key tasks in climate research at the present time is to separate anthropogenic effects from natural change. Solar variability is one possible cause of natural change in addition to other external phenomena such as volcanic eruptions and, on a long-term scale, orbital changes and celestial body impacts. The topic of "sun-weather relationships" has followed a long and tortuous history of scientific speculations and controversy since the continuous observation of sunspots began in the 17th century. It was not until recently that more systematic studies with long-term data bases of meteorological, climatological and solar parameters led to an increasing, statistically robust, body of evidence for a causal connection between some manifestations of solar variability and changes in the troposphere and the climate system. While of planetary' scale, the strength and sign of pertinent correlations have distinct geographic, seasonal and other temporal characteristics. Most likely, several trigger mechanisms are at work simultaneously, but their relative importance may depend on the time-scale envisaged and on competing processes such as volcanic eruptions. In this paper we will summarize the most frequently formulated criticisms, review the most recent results on relevant solar variability effects at the 11-year, secular, and short-term time scales, and discuss proposed mechanisms such as enhanced Hadley circulation, charged particle ionization effects on clear-air conductivity, and electric field effects on the microphysics of cloud formation.